2022
DOI: 10.1002/adtp.202200040
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing cGAS‐STING Pathway for Cancer Immunotherapy: From Bench to Clinic

Abstract: Recent advances in cancer immunotherapy have accomplished clinical successes in certain cancer models over the past decade. However, cancer treatments with adoptive cell transfer or immune checkpoint blockade (ICB) have shown critical limitations against solid tumors, which comprise the majority of human cancers. Thus, novel cancer immunotherapy which harnesses innate immunity process may be required in these tumor types. Cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) pathway, one of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 185 publications
0
4
0
Order By: Relevance
“…While TLR‐activating adjuvants are common in the clinical space, those that target other pathways, such as cyclic GMP‐AMP synthase stimulator of interferon genes (cGAS‐STING), Nod‐like receptor (NLR), and Rig‐I‐like receptor (RLR), are emerging as promising options for adjuvant combinations. The cGAS‐STING pathway is a cytosolic DNA sensing pathway of particular interest, since in recent years it has been shown to play a major role in tumor control 109–111 . Agents that act on this pathway stimulate type I interferon production in tumors, which drives downstream events including maturation of critical subsets of APCs (cDC1s), recruitment of T cells, and cross‐presentation to generate effective CD8+ T cells.…”
Section: Discussion Opportunities and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…While TLR‐activating adjuvants are common in the clinical space, those that target other pathways, such as cyclic GMP‐AMP synthase stimulator of interferon genes (cGAS‐STING), Nod‐like receptor (NLR), and Rig‐I‐like receptor (RLR), are emerging as promising options for adjuvant combinations. The cGAS‐STING pathway is a cytosolic DNA sensing pathway of particular interest, since in recent years it has been shown to play a major role in tumor control 109–111 . Agents that act on this pathway stimulate type I interferon production in tumors, which drives downstream events including maturation of critical subsets of APCs (cDC1s), recruitment of T cells, and cross‐presentation to generate effective CD8+ T cells.…”
Section: Discussion Opportunities and Challengesmentioning
confidence: 99%
“…The cGAS‐STING pathway is a cytosolic DNA sensing pathway of particular interest, since in recent years it has been shown to play a major role in tumor control. 109 , 110 , 111 Agents that act on this pathway stimulate type I interferon production in tumors, which drives downstream events including maturation of critical subsets of APCs (cDC1s), recruitment of T cells, and cross‐presentation to generate effective CD8+ T cells. However, their instability, poor membrane permeability, and toxicity have precluded their effective use as systemic agents.…”
Section: Discussion Opportunities and Challengesmentioning
confidence: 99%
“…Recently, STimulator of INterferon Genes (STING) has been identified as a potential “druggable” immunotherapeutic target for cancer treatment [ [17] , [18] , [19] ]. STING is an endoplasmic reticulum-associated homodimer protein and the receptor for 2′,3′-cyclic guanosine monophosphate–adenosine monophosphate (cGAMP) [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] As one of the most promising strategies to enhance the immunotherapeutic effect, recent studies have indicated the activation of the stimulator of interferon genes (STING) pathway. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%